Botulinum toxin and hyaluronic acid: Use and indications in the treatment of rejuvenation (Research, Society and Development, 2024)
The search for aesthetic procedures for facial improvements has grown considerably in recent years and the population's concern with maintaining beauty and delaying skin aging has given a great boost to advanced aesthetics. One of the most sought after procedures has been filling with Botulinum Toxin (TB) and Hyaluronic Acid (HA). The importance of studying this topic is that it has great relevance today due to the fact that the number of aesthetic procedures with of facial harmonization has increased. From this perspective, the increasingly frequent search for aesthetic procedures is emphasized, with the aim of achieving the desired results, more easily and through less invasive procedures that meet the patient's desires and needs. Therefore, the trained professional must have knowledge of risk zones for injectables for the purpose of, in-depth knowledge of the neuromuscular, arterial and venous anatomy (such as branches of the carotid artery, areas with extensive vascular anastomoses) and recognize signs and symptoms of complications, management for their prevention and treatment.